Implementasi Manajemen Keuangan Sekolah Dalam Rangka Meningkatkan Kualitas Pendidikan Di SMAN 5 Payakumbuh - Fatma Sari; Iswantir M; Susanda Febriani (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This article focuses on how financial management in educational institutions can be implemented. Management includes everything related to administrative control or management. In addition, this article discusses the different types of school finance management that are crucial to achieving educational goals and improving the quality of education. One way to improve the quality of education is by knowing the national education standards that apply in Indonesia. To ensure that educational institutions succeed, madrasah financial management must be handled seriously and responsibly. This will prevent undesirable outcomes and improve the quality of education